Raising Attainment With Diverse Students: An Inclusive Approach to the Teaching of Academic Literacy - Chiu, Tiffany; Rodriguez-Falcon, Olga (Journal of Academic Writing, 2018)
This research aims to evaluate the impact of an inclusive writing approach, which strives to embed academic literacy into subject curriculum, an initiative that ran across schools at a UK-based post-1992 university in 2015-16. As an exploratory investigation, this research drew on a redesigned social science transitional module, where academic writing provision is closely in line with the subject content and assessments. This project explores student perceptions and experiences of the embedded writing provision and the extent to which the intervention contributed to student attainment. Data were drawn from focus group discussions, where 41 students participated, and from student grades for the comparison of attainment rates across 2014-15 and 2015-16. The focus groups were analysed using NVivo 11 to identify key themes in relation to student views of the embedded academic literacy provision. Student grades were explored using MS Excel for the relative progress across academic years. The findings reveal the positive impact of the provision on students’ attainment and confidence as learners and writers in higher education. This paper concludes with pedagogical implications and a discussion of potential areas for further research to investigate the diversification of support modes as to accommodate different learning styles of students.